Wettability and Interfacial Tension Alteration through Surface-Modified Nanosilica using Anionic Surfactant for Enhanced Oil Recovery - AHMED, AFAQUE (2018)
Enhanced oil recovery (EOR) using nanoparticles has become a promising approach to produce the remaining oil from depleted fields. Advanced materials and additives are sought to make EOR economically feasible in reservoirs with challenging and harsh environments, i.e. high temperature, pressure and salinity.